Analysis of 500 Pesticide Residues in Milk and Infant and Young Children Formula Milk Powder by Ultra-high Performance Liquid Chromatography-Quadrupole-Time of Flight Mass Spectrometry - NING Xiao, ZHANG Jingran, JIN Shaoming, CAO Jin (Shipin Kexue, 2023)
Objective: An ultra-high liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-QTOF-MS) was established and applied for the screening and quantitation of pesticide residues in raw milk and infant and young children formula milk powder. Methods: A stable and reliable pretreatment procedure involving quick, easy, cheap, effective, rugged and safe (QuEChERS) extraction and Captiva EMR-lipid cleanup was developed and validated. The samples were separated on a Luna Omega Polar C18 (2.1 mm × 100 mm, 1.6 μm) by gradient elution using mobile phase A consisting of 2 mmol/L ammonium formate and 0.01% formic acid and mobile phase B consisting of 2 mmol/L ammonium formate and 0.01% formic acid. By analyzing commercial pesticide certified reference materials, a single injection method using two fragmentation techniques, collision-induced dissociation (CID) and electron activated dissociation (EAD) was developed for the simultaneous qualitative screening and quantitative analysis of 500 pesticide compounds, in which mass spectrometry data were collected using the Zeno sequential window acquisition of all theoretical fragment ion spectra (SWATH) data-independent acquisition (DIA) mode. Comprehensive scores obtained by the OS software from four factors, including mass deviation, retention time deviation, differential isotope ratio and spectrum library similarity, were used for qualitative screening. The matrix-matched external standard method was used for quantitative analysis based on the peak area of precursor ions in the extracted ion chromatogram (XIC). Results: The comprehensive scores of the 500 pesticides and their metabolites ranged from 90.4 to 99.4 points, higher than the minimum score of qualitative screening (90 points), and the limits of detection (LOD) were in the range of 0.025–0.5 μg/kg. The correlation coefficients (r2) of the matrix-matched calibration curves for 103 pesticides and their metabolites with maximum residue limits (MRL) in milk set by the national standard of China GB 2763-2021 were above 0.99. The average recoveries ranged from 72.7% to 114.5% at three spiked concentration levels with relative standard deviations (RSDs) of 2.1%–13.6% (n = 6), and the limits of quantitation (LOQ) were in the range of 0.15–3 μg/kg. Conclusion: This method was sensitive and accurate, and could be used for the screening identification of multiple pesticides and their metabolites and the quantitative analysis of restricted pesticides with high detection rate in raw milk and infant formula milk powder at low cost.